2019
DOI: 10.1186/s13223-019-0351-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis of recurrent wheezing in Chinese young children: a prospective cohort study

Abstract: Background Nearly all the investigations into the risk factors for wheezing and asthma were conducted in developed countries with a high prevalence rate of asthma and allergy, but the studies in developing countries are limited. In this study, we aimed to investigate the risk factors for different wheezing phenotypes in Chinese young children and to explore the prognosis of recurrent wheezing. Methods This cohort study contained the recruitment stage and the follow-up s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
6
0
3
Order By: Relevance
“…Matricardi et al 21 showed that the incidence of wheezing declines with age. Guo et al 22 found that the number of wheezing episodes decreases significantly during the follow-up stage and that the age at wheezing onset is earlier in those with transient wheezing than in those with persistent wheezing. The respiratory system gradually undergoes development with age, which may be an important reason for the decrease in the number of wheezing episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Matricardi et al 21 showed that the incidence of wheezing declines with age. Guo et al 22 found that the number of wheezing episodes decreases significantly during the follow-up stage and that the age at wheezing onset is earlier in those with transient wheezing than in those with persistent wheezing. The respiratory system gradually undergoes development with age, which may be an important reason for the decrease in the number of wheezing episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Следует отметить, что течение рецидивирующего бронхообструктивного синдрома в хронологическом аспекте в целом совпадает с возрастной динамикой симптомов бронхиальной астмы: с увеличением возраста ребенка снижается частота приступов при смехе, плаче, воздействии пищевых аллергенов, нарастает при физической нагрузке и аэросенсибилизации [33,34]. Аэросенсибилизация и коморбидный аллергический ринит как самостоятельно, так и в сочетании с риновирусной инфекцией служат наиболее клинически значимыми предикторами рецидивов бронхиальной обструкции [35,36].…”
Section: факторы риска развития рецидивирующего бронхообструктивного ...unclassified
“…Allergic rhinitis is common in children with asthma (de Groot et al, 2012;Price, 2010). Concurrent with the increase of childhood asthma in China, allergic rhinitis, and wheeze, a symptom suggestive of asthma, have also been increasing recently among children (Guo et al, 2019). A survey of ten cities in different geographic regions of China found that the prevalence of rhinitis varied from 24.0% to 50.8%, while the prevalence of wheeze varied from 13.9% to 23.7% (Zhang et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%